Ghana - Utley, Ian (London Kuperard, 2015)
These concise guides tell you what to expect, how to behave, and how to establish a rapport with your hosts. This inside knowledge will enable you to steer clear of embarrassing gaffes and mistakes, feel confident in unfamiliar situations, and develop trust, friendships, and successful business relationships.
"The essential guide to customs & culture"--Cover.
Includes bibliographical references and index.
Keywords: Etiquette -- Ghana -- Handbooks, manuals, etc; Ghana -- Social life and customs -- Handbooks, manuals, etc; Ghana -- Guidebooks; Ghana -- Description and travel